The 2003 Ms6.1 Minle Earthquake: An Earthquake in the Minle-Yongchang Reverse Fault-Related Fold Belt in the Hexi Corridor, NW China - Zou, Xiaobo; Yuan, Daoyang; Shao, Yanxiu; Liu, Xingwang; Ge, Weipeng; Zhang, Bo (Frontiers in Earth Science, 2021)
The Minle-Yongchang fault is an active reverse fault-related fold structural belt developed in the Hexi Corridor Basin on the northeastern edge of the Tibetan Plateau. An earthquake of Ms6.1 occurred near the Minle-Yongchang fault zone in 2003. The deformation pattern of the Minle-Yongchang fault and its relationship with this strong earthquake, however, are still not well known. In this study, we used the methods of HYPOINVERSE absolute location and double-difference location with waveform cross-correlation technology to relocate the 2003 Minle earthquake sequence. In total, 383 earthquakes are precisely relocated. Based on the results of precise seismic relocation, using the method of determining fault planes by small earthquakes, the seismogenic fault is found to be a low-angle thrust with a strike of 311°, a dip of NE, and a dip angle of 14°. It does not rupture the surface, extends to 19–20 km depth, and is hidden beneath the Yonggu Anticline. We also employed the cut-and-paste (CAP) method with a broadband waveform to determine the focal mechanism of the mainshock in 2003: the strike is 311°; the dip is 34°; and the rake is 90°. The fault plane parameters obtained in these two ways are roughly consistent. We also used a digital elevation model (DEM) derived from the SPOT 6 stereo image pair and high-precision differential Global Positioning System (GPS) to measure the displacement of terraces. Topographic profiles along the terraces across the Minle-Yongchang fault show that high alluvial terrain exhibits fold deformation. The vertical offsets of the T2 and T3 terraces along the Tongziba River are approximately 2.3 and 22 m, respectively. Optically stimulated luminescence (OSL) dating indicates that the ages of T2 and T3 are 11.3 and 106 ka, respectively. We calculated an average uplift rate of 0.21 ± 0.05 mm/a by dividing the vertical offset by age. According to the spatial distribution of the relocated earthquake sequence and terrace deformation in the study area, the Ms6.1 Minle earthquake in 2003 was caused by the latest activity of a blind reverse fault-related fold in the Hexi Corridor Basin.